The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/jeppm-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Challenges of Internet of Things on Construction Projects Using Fuzzy Approach

Abstract: This study presents a fuzzy decision-making trial and evaluation laboratory (DEMATEL) analysis of the internet challenges of the internet of things (IoT) implementation of construction projects in Nigeria. The identification of the IoT challenges was carried out through a thorough literature search and discussions with 27 built environmental experts. In addition, DEMATEL, an expert judgement-based tool, was used to pick, design, and evaluate a structural model consisting of a causal relationship between define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The discovery that technical barriers substantially influence IoT implementation in advancing smart constructions and infrastructure within the construction sector aligns with a prior study that has recognized technical hindrances to adopting IoT. Amade & Nwakanma (2021) [ 43 ]conducted a study that revealed that technical barriers, including interoperability and integration with legacy systems, were major impediments to the adoption of IoT in the construction sector. This study's distinctive contribution lies in its concentration on building sector and its recognition of particular technical barriers exclusive to this setting, such as industry fragmentation and coordination [ 24 , 56 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The discovery that technical barriers substantially influence IoT implementation in advancing smart constructions and infrastructure within the construction sector aligns with a prior study that has recognized technical hindrances to adopting IoT. Amade & Nwakanma (2021) [ 43 ]conducted a study that revealed that technical barriers, including interoperability and integration with legacy systems, were major impediments to the adoption of IoT in the construction sector. This study's distinctive contribution lies in its concentration on building sector and its recognition of particular technical barriers exclusive to this setting, such as industry fragmentation and coordination [ 24 , 56 ].…”
Section: Discussionsupporting
confidence: 55%
“…Subsequently, a preliminary survey was administered to assess the dependability and authenticity of the survey instrument. The results were subjected to Exploratory Factor Analysis (EFA) to detect any possible shortcomings in the questionnaire [ 43 , 56 ]. The questionnaire for the main survey was modified based on the pilot survey results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation